Claudia and the new girl - Martin, Ann M.; Epstein, Gabriela (2021)
"Claudia has always been the most creative kid in her class... until Ashley Wyeth comes along. Ashley's really different: she wears hippie clothes, has multiple earrings, and she's the most fantastic artist Claudia has ever met. Ashley says Claudia is a great artist, too, but thinks she's wasting her artistic talent with The Baby-sitters Club. When Claudia starts spending more time with Ashley and missing BSC meetings, it becomes clear that Claudia has to make a decision -- one of them has to go!"--
Ages 8-12
Grades 4-6